Features of Family Environment of a Child in Post-Industrial Society - A. D. Andreyeva (Научный диалог, 2018)
The problem of transformations undergone by the family environment in the countries of the post-industrial economy is analysed. The most significant highlighted changes are those related to the reduction of quantitative and generational composition of a family, weakening of the idea of child-centrism, search for new models of active parenting, slow growing up of children in the comfort of a modern family environment. The socio-evolutionary nature of changes in the family standard, determined by the level of economic, social and cultural development of society, is emphasized. It is shown that the new social situation of parenthood is determined by fundamental changes in the architecture of socio-economic relations in post-industrial society. It is characterized by two main trends: an increase in the number of unemployed young women seeking self-realization in the field of parenthood, and an active family care for the future of the child in a highly competitive society. The risks of personal development of children associated with the implementation of the model of active parenthood are: reducing the initiative, responsibility and independence of modern adolescents and young men. It is suggested that active parenthood has an impact on the composition of the family environment, which is now determined not only by family ties and relationships, but also by the ideological proximity of its members. Real and networked parent communities not only expand the environment of the modern family, but also work out the variable models of parenthood, filling the empty niche of the social standard of family education.